2020
DOI: 10.1016/j.amjcard.2020.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Percutaneous Coronary Intervention in Patients With Crohn's Disease and Ulcerative Colitis (from a Nationwide Cohort)

Abstract: Patients with inflammatory bowel disease (IBD) are at an increased risk of ischemic heart disease. However, there is limited evidence on how their outcomes after percutaneous coronary intervention (PCI) compare to those without IBD. All PCI-related hospitalizations from the National Inpatient Sample between 2004 and 2015 were included, stratified into three groups: no-IBD, Crohn's disease (CD) and ulcerative colitis (UC). We assessed the association between IBD subtypes and in-hospital outcomes. A total of 6,6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…We observed that SMuRF-less patients were younger, more likely to be male and had a lower BMI with less complex coronary artery disease. This high rate of patients with significant coronary artery disease requiring PCI but without ‘traditional’ risk factor should encourage further research to identify other risk factor, such as (but not limited to) inflammatory diseases [13] , [14] . As out results are based on a cohort, we could not assess the prevalence of inflammatory disease in the SMuRFless population of to look at other factors as CRP.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that SMuRF-less patients were younger, more likely to be male and had a lower BMI with less complex coronary artery disease. This high rate of patients with significant coronary artery disease requiring PCI but without ‘traditional’ risk factor should encourage further research to identify other risk factor, such as (but not limited to) inflammatory diseases [13] , [14] . As out results are based on a cohort, we could not assess the prevalence of inflammatory disease in the SMuRFless population of to look at other factors as CRP.…”
Section: Discussionmentioning
confidence: 99%
“…Previous large-scale retrospective studies in Australia, Finland, and the United States reported the prevalence of RA and SLE as 0.9–2.8% and 0.1–0.4% among patients with acute MI [ 9 12 ], which is in line with our results. Similarly, in a nationwide PCI cohort in the United States, IBDs (Crohn’s disease and ulcerative colitis) were found in 0.3% [ 18 ]. A prospective registry in France evaluated long-term ischemic outcomes after ST-segment elevation MI in patients with integrated chronic inflammatory diseases (prevalence 4.6%), in which RA was a leading disorder (1.0%) as was seen in the present study and others, but psoriasis (0.9%), ankylosing spondylitis (0.9%), and giant cell arteritis (0.8%) were the second common disorders among CSIDs [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…An inpatient healthcare database study in the United States showed that among patients undergoing PCI, the presence of autoimmune rheumatic diseases such as RA, SLE, and SSc was associated with an increased risk of in-hospital bleeding events, especially in those with SLE and SSc [ 17 ]. With the same inpatient database, the presence of IBDs was also reported to be related to bleeding risks during hospitalization [ 18 ]. Although these findings suggested a predisposition to bleeding in patients with CSIDs, major bleeding outcomes during hospitalization did not differ significantly between those with and without CSIDs in the present study, and data on long-term bleeding events are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the study of Kobo O. et al assessed the complications following the supercutaneous coronary intervention in IBD patients. This study showed that IBD was associated with a lower risk of in-hospital complications following percutaneous coronary intervention (PCI) other than severe haemorrhage [ 41 ], which indicates that appropriate and effective treatment of IBD may be the basis for reducing the risk of ACS and reducing complications after PCI.…”
Section: Cardiovascular Risk In Patients With Ibdmentioning
confidence: 99%